Analisis Penerapan Sistem Agroforestri Kopi: Studi Lapangan Agrotech dan Perspektif Petani Di Bener Meriah Fox Jumps Over The Lazy Dog: The Quick Brown Fox Jumps Over The Lazy Dog (Isolation And Analysis Of Proteolytic Activity Of Local Actinomycetes Fro - Audina Yoeliarniza; Amirunnas Amirunnas; Alia Arifina; Raudhatul Jannah; Nana Fadhliana; Nikitha Chairunnisa; Indry Malliny; Salsabila Firdausia; Cut Hadisti Arhafna; Nanda Zamzami (Jurnal Bioleuser, 2025)
Agroforestry integrates crops, trees, and livestock to enhance land productivity and ensure sustainability. Bener Meriah Regency faces challenges in conventional coffee cultivation, including price fluctuations, pest infestations, and climate change impacts. This study analyzes the implementation of coffee agroforestry at PT. DOR Agritech and among local farmers using a descriptive qualitative method. The findings reveal that agroforestry increases farmers’ income through crop diversification, improves soil fertility, reduces dependence on chemical inputs, and strengthens ecosystem resilience. A comparison between large-scale practices and smallholder farmers highlights variations in strategies, with key challenges in waste management and companion crop selection. These results emphasize the need for policy support and locally tailored strategies to establish agroforestry as an adaptive, sustainable, and profitable model for coffee farming.